Strengthening Madrasah Fortresses by Enforcing Religious Moderation as a Professional Standard for Teachers - Setiyono (AMUYA: JOURNAL OF MANAGEMENT, 2025)
Madrasahs, envisioned as bastions of national values, face a critical challenge in implementing religious moderation in Jambi Province. A significant gap exists between national policy mandates and on-the-ground realities, rooted in the low competency and wide disparity in teachers' understanding. Data from the 2022 Competency Assessment (CAT) reveals that over 31% of teachers have 'Poor' or 'Very Poor' comprehension, creating an institutional vulnerability that transforms madrasahs into environments susceptible to intolerant narratives. This study employs a qualitative policy analysis method. The problem was analyzed using secondary data and prioritized with the USG (Urgency, Seriousness, Growth) method. Policy alternatives were evaluated using William N. Dunn's effectiveness criteria to produce a strategic recommendation. The findings indicate that the core problem is structural: religious moderation competency has not been integrated as a measurable professional performance standard within the Teacher Performance Appraisal (PKG) system and academic supervision. Consequently, the most effective and efficient intervention is to revitalize the existing system. It is recommended that the Head of the Jambi Provincial Office of the Ministry of Religious Affairs issue a Circular Letter and Technical Guidelines to integrate practical indicators of religious moderation into the PKG and supervision instruments. This measure fundamentally shifts religious moderation from a moral appeal to a mandatory, evaluable, and accountable professional standard, thereby reinforcing the role of madrasahs as epicenters for nurturing moderate and inclusive national values.